Representasi Sosok Tom Cruise dalam Film Top Gun: Marverick (Analisis Semiotika Roland Barthes) - Irfan Tito; Ade Budi Santoso (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This research analyzes the representation of Tom Cruise's figure in the film "Top Gun: Maverick" by using Roland Barthes' semiotic approach. The main focus of this research is to understand how the character of Maverick played by Tom Cruise is represented through various signs and symbols in the film. The method of analysis used is semiotic analysis, which allows researchers to identify the signs and symbols used in representing the character. This research uses a qualitative approach by analyzing various visual, narrative, and contextual elements in the film. The findings of this research reveal how Tom Cruise as an actor and the character of Maverick are represented in the context of relevant culture and ideology. The results of this analysis provide a deeper understanding of how the character is understood and accepted by the audience, as well as the implications of his representation in a broader social and cultural context. This research contributes to the understanding of how symbols in popular media such as movies can shape our perception and understanding of certain characters in popular culture.